Pyrometallurgical Principles - Shamsuddin M.; Sohn H.Y. (My University, 2025)
The prime objective of this article is to demonstrate the significant role of physicochemical principles in the development and improvement of extraction technologies for different types of nonferrous metals categorized as common, reactive, rare, and refractory. We demonstrate the roles of phase rule, free energy and activity in the pyrometallurgical processes, such as reduction, roasting, smelting, and refining of different metals. Based on the discussions in the following sections, the reader will appreciate the contributions of phase rule, activity and free energy in the selection of particular steps in the extraction of different types of metals. The article also demonstrates how difficult reactions like the removal of nickel from blister copper can be made feasible by generating conditions according to Van't Hoff isotherm. Continuing development of new technologies and reduction in number of steps in the production of copper, lead, zinc, and nickel have been possible by the thorough understanding and application of the physical chemistry of reactions involved in different extraction steps. The theoretical bases behind the development of several new technologies and the difficulties in realizing certain worthwhile concepts into industrial practices are explained. © 2024 Elsevier Ltd. All rights reserved.